PUSAT TERAPI OKSIGEN DENGAN PENERAPAN KONSEP GREEN BUILDING DI PULAU GILI IYANG MADURA - Vivi Aida; Amin Sumadyo; Ummul Mustaqimah (Universitas Sebelas Maret Surakarta, 2017)
Abstract: Gili Iyang Island has high oxygen level potential which is more than 20% with lower pollution percentage compared to other regions in Indonesia. The result of oxygen in Gilli Iyang Island was done by LAPAN in 2006 and BBTKL-PP in 2013. It reached 20,9% up to 21,5%. The oxygen level affects Gili Iyang Island becoming tourist destination to take oxygen therapy. However, the activity isn’t supported by adequate facilities, so that an oxygen therapy center is necessary to meet those needs. The design proposal rises a problem is designing a healthy oxygen therapy facility that hold the local natural circumstance. Environmental issues in Gili Iyang Island which is still pure and healthy responded by Green Building concept application in Oxygen Therapy Center. The Oxygen Therapy Center focusing on the application of green building concept to respond the environmental issue of Gili Iyang Island. The Green Building concept based on six criterias in accordance with the Greenship: Green Building Council Indonesia (GBCI): appropriate land use, energy efficiency and conservation, water conservation, resource and material cycle, health and comfort in space, and environmental management building. The concept is trying to afford a healthy and nature-synergy building design so than it can support oxygen therapy process and energy-saving building. The main design concepts are site cultivation, mass system, shape and appearance of the building, material selection, exterior of the building, also building utilities. Keywords: Gili Iyang Island, Oxygen Therapy, Green Building Concept, Greenship: Green Building Council Indonesia (GBCI)